Effect of floor type and bedding system on sows lifespan - Soltész, Angéla (Acta Agraria Debreceniensis, 2013)
The paper studies two nucleus pig farms in the Great Plain region of Hungary which have same management, same feeding system but different breeding technology (Farm A had solid floor with straw and Farm B had slatted floor without straw). The genetics of sows were crossbred Dutch Large White and Dutch Landrace. The comparative examination was based on the causes of culling according to the different floor type. To the analysis of culling reasons was applied the methods of survival analysis.In the analysis there were used the Kaplan-Meier method and the Cox Proportional Hazard model to the estimate the difference between the farms. The results of survival analysis showed significant difference (p